2013
DOI: 10.3390/nu6010111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipid Emulsions in Parenteral Nutrition of Esophageal Cancer Surgical Patients Receiving Enteral Nutrition: A Comparative Analysis

Abstract: Background: Olive oil-based lipid emulsion (LE) and medium chain triglyceride/long chain triglyceride (MCT/LCT) emulsion are both LEs with low ω-6 polyunsaturated fat acids (PUFAs) content. However, which one of these LEs is associated with a lower infection risk in patients receiving parenteral nutrition (PN) remains unclear. The aim of the study was to compare the effects of the two LEs in PN in esophageal cancer patients undergoing surgery. Methods: Patients with resectable esophageal carcinoma were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Of two studies reporting on total bilirubin, one reported that olive oil-based ILE significantly decreased total bilirubin levels from baseline, whereas the other reported no change; however, the levels were within normal limits [ 38 , 71 ]. Similar findings for liver function tests have been reported for severely malnourished adult patients [ 73 ], adult patients receiving long-term PN [ 39 , 90 ], adult patients with esophageal cancer [ 92 ], and adult patients with severe burns [ 35 ].…”
Section: Liver Functionsupporting
confidence: 80%
See 1 more Smart Citation
“…Of two studies reporting on total bilirubin, one reported that olive oil-based ILE significantly decreased total bilirubin levels from baseline, whereas the other reported no change; however, the levels were within normal limits [ 38 , 71 ]. Similar findings for liver function tests have been reported for severely malnourished adult patients [ 73 ], adult patients receiving long-term PN [ 39 , 90 ], adult patients with esophageal cancer [ 92 ], and adult patients with severe burns [ 35 ].…”
Section: Liver Functionsupporting
confidence: 80%
“…We identified 24 studies [ 20 , 33 , 35 , 38 , 39 , 41 , 43 , 44 , 45 , 46 , 51 , 61 , 64 , 71 , 72 , 73 , 75 , 85 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ] and three meta-analyses [ 66 , 81 , 83 ] that investigated the effects of olive oil-based ILE on liver function ( Table 5 ). Findings have varied across studies, and no clear pattern of effect of olive oil-based ILE on markers of liver function (sometimes called liver function tests) such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), and bilirubin (total or conjugated) or on biliary tract function markers such as alkaline phosphatase (ALP) and gamma-glutamyl transpeptidase (GGT) have been discerned.…”
Section: Liver Functionmentioning
confidence: 99%
“…We grouped the published studies into three groups (Table 1) [34567891011121314151617181920212223242526272829303132333435363738394041424344454647484950515253545556575859606263646566676869707172737475767778798081]. The first group included studies that identified the characteristics of hosts exhibiting inflammation, the second group included studies that measured the effect of treatment interventions, and the third group included studies that predicted the outcomes of interventions.…”
Section: Factors Associated With Inflammation In Patients With Cancermentioning
confidence: 99%
“…Historically, laboratory values are used to assess the inflammatory status of the patients (Table 2) [317232634353839424450596266697173747576777879848687888990919293949596979899100101102103104105106]. Laboratory parameters are economical to evaluate, easily measurable, repeatable, and ready to use in daily clinical practice.…”
Section: Approaches For Evaluating Inflammatory Parametersmentioning
confidence: 99%
See 1 more Smart Citation